Transformasi Pendidikan Islam dalam Konteks Globalisasi dan Modernisasi: Sebuah Analisis Filsafat - Arif Wafa Al Faris; Zahrotul Mila; Siti Khumairoh; Ahmad Husin (CV. Lentera Literasi Indonesia, 2026)
This study examines the transformation of Islamic education in the context of globalization and modernization from the perspective of Islamic educational philosophy. Employing a qualitative research design, this study adopts a library-based research method. Data are analyzed using a descriptive–critical approach through content analysis to explore the interrelationship between Islamic values and the demands for educational transformation in the global era. The findings reveal that the transformation of Islamic education must be grounded in a robust philosophical framework encompassing ontological, epistemological, and axiological dimensions. Furthermore, the transformation process necessitates a paradigm shift from traditional educational models toward interdisciplinary knowledge integration, the development of adaptive and responsive curricula, and the ethical and responsible adoption of educational technologies. Consequently, Islamic education is expected to cultivate Muslim individuals who are spiritually grounded, intellectually competent, morally upright, and capable of engaging effectively in a globalized world.